MR imaging of articular cartilage at 1.5T and 3.0T: comparison of IDEAL 2D FSE and 3D SPGR with fat-saturated 2D FSE and 3D SPGR in a porcine model. (May 2014) - Cha, Jang Gyu; Yoo, Jae Ho; Rhee, Sun Jung; Hwang, Seung Sik; Han, Jong Kyu
Background: IDEAL technique is a robust fat-water separation method which is potentially useful in cartilage imaging with significant improvement in the cartilage signal-to-noise ratio (SNR). Purpose: To identify whether iterative decomposition of water and fat with echo asymmetry and least-squares estimation (IDEAL) improved diagnostic performance for IDEAL 2D fast spin echo (FSE) and 3D spoiled gradient-recalled echo (SPGR) versus fat-saturated (FS) protocols at 1.5 and 3.0 T in the evaluation of patella-femoral cartilage lesions. Material and Methods: Forty-six artificial cartilage lesions were created in femoro-patellar articular cartilages of 11 porcine knees. All knees underwent MR examination at 1.5 and 3.0 T with MR protocol consisting of sagittal FS 2D FSE and 3D SPGR and IDEAL 2D FSE and IDEAL 3D SPGR, respectively. Qualitative assessment was performed to compare the diagnostic performance between 1.5- and 3.0-T protocols and between IDEAL and FS protocols. Results: IDEAL 3D SPGR had a significantly higher accuracy for detecting partial thickness cartilage lesions ( P  < 0.01) than FS SPGR protocols, whereas there was no significant difference in diagnostic performance between IDEAL and FS 2D FSE except for one cartilage lesion. For all imaging sequences, no significant difference was observed in the diagnostic performance between 1.5- and 3.0-T imaging protocols ( P  = 0.42–0.91). Conclusion: Compared with conventional FS SPGR imaging, IDEAL 3D SPGR provided a better diagnostic performance for evaluation of porcine knee articular cartilage lesions in the knee joints at 1.5 and 3.0 T. IDEAL 3D SPGR may therefore be useful for detecting partial-thickness cartilage lesions in patients with degenerative osteoarthritis.